Bibliometric Analysis of The Development Map and Direction of Contemporary Learning Research in The Scopus Database 1976-2024 - Robbaniyah, Qiyadah; Barry, Aboubacar; Khanom, Jobeda (Multicultural Islamic Education Review, 2025)
This study aims to analyze the development map and research direction related to Contemporary Learning through a bibliometric analysis method with a descriptive approach. Data was collected from the Scopus database in the 1976–2024 period using tools such as R, RStudio, VOS viewer, and Microsoft Excel. The results of the analysis show a significant increase in scientific publications since the early 2000s, with the largest surge occurring in the 2020–2024 period. The United States, the United Kingdom, and Australia were major contributors to the study, with universities such as Monash University leading academic publications. Core themes such as learning, curriculum, and e-learning are identified as key focuses, while subthemes such as machine learning and learning systems offer innovation potential for future research. The analysis of the keyword network highlights that technology-based learning, sustainability, and collaborative approaches play an important role in contemporary education. This study concludes that Contemporary Learning is a growing field with high relevance to digital transformation and global education challenges, providing opportunities for researchers to explore innovative themes that support the development of modern education.